Fatigue behavior of uncorroded non-load-carrying bridge weathering steel Q345qDNH fillet welded joints. (January 2020) - Su, Han; Wang, Jian; Du, Jinsheng
Abstract: Bridge weathering steel produced in China is being increasingly employed in bridges worldwide, Q345qNH is among the most commonly used steel grades. Fatigue behavior of uncorroded non-load-carrying fillet welded joints made of bridge weathering steel Q345qNH was explored in this paper. Fatigue tests were conducted on 10 specimens which were under 7 stress ranges, S–N curve and its lower bound of 95% survival probability were established. It was observed that the design S–N curve for non-load-carrying fillet welded joint in Eurocode 3 is suitable to evaluate fatigue behavior of this batch of specimens and offers a considerable safety margin. The influences of initial crack size, initial crack shape, initial crack location and misalignment of attachments on fatigue behavior of non-load-carrying fillet welded joints were explored, the relationship between fatigue life and initial crack size was derived. Furthermore, it is recommended to adopt a semi-elliptical crack with initial crack depth of 0.075 mm for numerical simulation when initial crack size is unknown. The fatigue test results provide reference for fatigue design of steel bridges made of coated weathering steel and serve as control to analyze deterioration of fatigue behavior caused by corrosion for corroded non-load-carrying fillet welded joints made of uncoated weathering steel. Highlights: Fatigue behavior of uncorroded non-load-carrying fillet welded joints made of bridge weathering steel was investigated. Experimental S–N curve and its lower bound of 95% survival probability were established. It is recommended to adopt a semi-elliptical crack with initial crack depth of 0.075 mm for numerical simulation.